Gaps in Human Behaviour in Fires Research : A Scoping Review - Kinkel, Erica; van der Wal, C. Natalie; Ronchi, Enrico ; 0000-0002-2789-6359; Kuligowski, Erica D. (Fire Technology, 2025)
When developing a research roadmap for human behaviour in fires, it is necessary to identify areas that require additional research. A general overview – from a multidisciplinary perspective – of gaps in human behaviour in fires research across multiple contexts is missing. The goal of this paper was to perform a scoping review to identify research gaps and themes in all aspects of human behaviour in fires across contexts. This scoping review included 17 articles. In total, 37 research gaps and 11 research themes for the built environment and community context were identified. The main research gaps are related to cognitive factors, behavioural responses, environmental factors and physical/physiological factors. Also, for all research themes, additional research involving heterogenous populations is required. Furthermore, there is an imbalance in human behaviour in fires studies: most articles were focused on the built environment rather than the community context. Finally, the topic of intoxication has received limited research attention, and data collection methods lack diversity. Future research should not only be done from a multidisciplinary perspective but also interdisciplinary research efforts are required. The availability of more data and knowledge on human behaviour and responses in fires could be beneficial to simulation model developers/users, the general public and fire safety managers.
Keywords: Built environment; Community context; Evacuation; Fires; Human behaviour; Scoping review